2016
DOI: 10.1039/c5ra23731a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/vinyl ester resin nanocomposite: the effect of graphene oxide, curing kinetics, modeling, mechanical properties and thermal stability

Abstract: The Ea value of cure reaction of the GO/VE nanocomposite decreased. It is concluded that the GO acted as catalyst in the reaction of VE/GO nanocomposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…This value is acceptable, since the experimentally determined elongation at break is reported to range between 3.36% and 5.60% of strain. 7,9,48 The Young's modulus values increased with bond conversion: 3.36, 4.11, and 4.73 GPa for the samples with bond conversion of 50%, 70%, and 90%, respectively. This could be ascribed not only to the increase in bond conversion but also to the increase in the average number of cross-links per chain resulting in a more rigid 3D network Experimentally reported Young's modulus values vary between 2.50 and 3.52 GPa.…”
Section: Terminationmentioning
confidence: 99%
“…This value is acceptable, since the experimentally determined elongation at break is reported to range between 3.36% and 5.60% of strain. 7,9,48 The Young's modulus values increased with bond conversion: 3.36, 4.11, and 4.73 GPa for the samples with bond conversion of 50%, 70%, and 90%, respectively. This could be ascribed not only to the increase in bond conversion but also to the increase in the average number of cross-links per chain resulting in a more rigid 3D network Experimentally reported Young's modulus values vary between 2.50 and 3.52 GPa.…”
Section: Terminationmentioning
confidence: 99%
“…Isoconversional kinetic analysis has indicated that addition of the clays affects the reaction mechanism, in particular suppressing a transition to diffusion control. Arabli and Aghili have reported that the curing reaction of a vinyl ester monomer decelerates (shifts to higher temperature) on addition of 0.3 wt% of graphene oxide. Nevertheless, the isoconversional activation energy has been found to decrease significantly in the presence of graphene oxide.…”
Section: Polymerization and Crosslinkingmentioning
confidence: 99%
“…There is a large number of studies conducted to investigate properties of vinyl ester resin reinforced by micro/nano particles. Vahid Arabli et al studied in curing kinetics, modeling, mechanical properties and thermal stability in graphene oxide/vinyl ester resin nanocomposite [13]. They claimed that with a low content of graphene oxide (0.3%), the matrix became stiffer while the glass transition temperature shifted to a higher value.…”
Section: Introductionmentioning
confidence: 99%